Advances on two serological assays for human papillomavirus provide insights on the reactivity of antibodies against a cross-neutralization epitope of the minor capsid protein L2 - Mariz, Filipe Colaco; Putzker, Kerstin; Sehr, Peter; Müller, Martin (Frontiers in Immunology, 2023)
A second generation of prophylactic human papillomavirus (HPV) vaccines based on the minor capsid protein L2 has entered clinical trials as promising alternative to meet the gaps left out by the current vaccines concerning type-restricted protection, high costs and low penetrance in immunization programs of low-and middle-income countries. Most of the serological assays available to assess anti-HPV humoral responses are, however, not well suited for measuring vaccineinduced anti-L2 antibody responses. In this work, we have advanced our automated, purely add-on High-Throughput Pseudovirion-Based Neutralization Assay (HT-PBNA) in an L2-oriented approach for measuring antibody-mediated neutralization of HPV types 6/16/18/31/33/52/58. With the optimized settings, we observed 24-to 120-fold higher sensitivity for detection of neutralizing Ab to the L2 protein of HPV6, HPV16, HPV18, and HPV31, compared to the standard HT-PBNA. Alternatively, we have also developed a highly sensitive, cell-free, colorimetric L2-peptide capture ELISA for which the results were strongly concordant with those of the advanced neutralization assay, named HT-fc-PBNA. These two high-throughput scalable assays represent attractive approaches to determine antibody-based correlates of protection for the HPV L2 vaccines that are to come.